(untitled) (Revista Brasileira de Contabilidade e Gestão, 2020)
The objective of this study is to analyze the infrastructure, services and products offered by supermarkets to satisfy elderly consumers expectations. We conducted a quantitative-descriptive study with a sample of 100 people aged over 60 years, of both sexes. The sampling technique used was not a convenience probabilistic - it was performed in three supermarkets in Campo Grande, Mato Grosso do Sul, Brazil. The data was analysed by exploratory factor analysis and cluster analysis. The results show that the three supermarkets partially meet consumer expectations. Three market segments was identified. Segment 1 comprises 26% of the sample. In this group, the percentage of women was around 73%, the largest share receiving a minimum salary. This group proved to be more satisfied than others. Segment 2 is made up of 44% of respondents. Segment 3 is made up of 30% of respondents. In this segment, 76% of respondents are women. This group is the most dissatisfied. Besides this results, it is necessary for managers to further investigate this group of consumers in order to better understand their wants and needs.